Reliability of the CINtecTM p16INK4a immunocytochemical test in screening cervical precancerous lesions - Jović Milena; Nenadić Dane; Magić Zvonko; Zoltarevski Lidija; Đurđević-Vukomanović Biserka; Tatomirović Željka; Strelić Nataša; Vojvodić Danilo (Vojnosanitetski Pregled)
Background/Aim. Overexpression of p16INK4a has been found to be linked with genomic integration of high-risk human papillomavirus (HPV) and the developement of precancerous cervical intraepithelial lesions. The aim of this study was to examine is there a higher positive level of correlation between grade of histological dysplasia and p16INK4a level of expression in cervical smear, compared to results of Papanicolaou test. We also examined the correlation between HPV type, p16INK4a expression and Papanicolau test results. Methods. A total of 48 women with precanceorous cervical lesions and HPV cervicitis and 10 healthy women were enrolled in the study. Papanicolaou test, CINtecTM p16INK4a citological immunohistochemical test, polymerase chain reaction (PCR) HPV 16, 18, 31, 33 analysis and histopathology of the lesion were performed in all the patients. Results. Comparing the results of Papanicoulaou test and the grade of histological dysplasia, low-grade squamous intraepithelial lesion (LSIL) was confirmed in 38%, and high-grade squamous intraepithelial lesion (HSIL) in 69.2% of the patients (p > 0.05). Significant positive correlation was found between p16 overexpression and grade of histological dysplasia (p = 0.000). Overexpression p16 was found in 70% of LSIL and 94.4% of HSIL. Positive correlation was found between p16 overexpression and grade of dysplasia in Papanicolaou test (p = 0.011). In 38% of LSIL and 15% of HSIL cases p16 was not expressed. The most frequently found HPV type in PCR analysis was HPV16. Analysing the results of p16 test according to HPV status and Papanicolaou test rather heterogenous results were obtained. Conclusion. In the patients with precancerous cervical lesions a higher level of correlation was found between the grade of histological dysplasia and p16INK4a level of expression in the cervical smear, compared to the results of Papanicolaou test.